Slightly dirty maths: the richly textured mechanisms of impact - Meagher, L; Martin, U (Oxford University Press, 2017)
This empirical study explored how research can generate impacts by investigating different sorts of impacts from one academic field - mathematics - and the diverse mechanisms generating them. The multi-method study triangulated across: 1,2) content analysis of impact case studies and environment descriptions submitted to the UK Research Excellence Framework (REF) assessment; 3,4) a survey and focus group of heads of mathematics departments; 5) semi-structured interviews. Mathematics has had a full range of impact types, particularly conceptual impacts, although more tangible instrumental impacts were prioritised for REF. Multiple mechanisms were utilised, but seldom appeared in REF case studies. Long-term relationship-building and interdisciplinarity are particularly important. Departmental culture and certain knowledge intermediaries can play pro-active roles. In sharp contrast to simplistic linear narratives, we suggest that appreciation of diverse impact types, multiple, often informal, mechanisms and dynamic environments will enhance the likelihood of meaningful impacts being generated.